Aversive emotional interference impacts behavior and prefronto-striatal activity during increasing attentional control - Papazacharias, Apostolos; Taurisano, Paolo; Fazio, Leonardo; Gelao, Barbara; Di Giorgio, Annabella; Lo Bianco, Luciana; Quarto, Tiziana; Mancini, Marina; Porcelli, Annamaria; Romano, Raffaella; Caforio, Grazia; Todarello, Orlando; et al. (Frontiers in Behavioral Neuroscience, 2015)
Earlier studies have demonstrated that emotional stimulation modulates attentional processing during goal-directed behavior and related activity of a brain network including the inferior frontal gyrus and the caudate nucleus. However, it is not clear how emotional interference modulates behavior and brain physiology during variation in attentional control, a relevant question for everyday life situations in which both emotional stimuli and cognitive load vary. The aim of this study was to investigate the impact of negative emotions on behavior and activity in inferior frontal gyrus and caudate nucleus during increasing levels of attentional control. 22 healthy subjects underwent event-related functional magnetic resonance imaging while performing a task in which neutral or fearful facial expressions were displayed before stimuli eliciting increasing levels of attentional control processing. Results indicated slower reaction time and greater right inferior frontal gyrus activity when fearful compared with neutral facial expressions preceded the low level of attentional control. On the other hand, fearful facial expressions preceding the intermediate level of attentional control elicited faster behavioral responses and greater activity in the right and left sides of the caudate. Finally, correlation analysis indicated a relationship between behavioral correlates of attentional control after emotional interference and right inferior frontal gyrus activity. All together, these results suggest that the impact of negative emotions on attentional processing is differentially elicited at the behavioral and physiological levels as a function of cognitive load.